REASONS OF ADOPTION OF THE LITHUANIAN STATUTES OF XVITH CENTURY, THEIR RELATIONSHIP WITH 1569 UNION OF LITHUANIAN GRAND DUCHY WITH POLISH KINGDOM AND LITHUANIAN PARLIAMENTARISM FEATURES OF THE EPOCH - Vaičaitis, Vaidotas A. A. (Teisė, 2015)
Some novelty of this paper lays in the fact, that the XVIth century Lithuanian Statutes (or the Statutes of Grand Duchy of Lithuania) of 1529, 1566 and 1588 have been analyzed so far from historic, but not from legal and constitutional point of view. Therefore, historiographical approach concerning the Lithuanian Statutes was important, but not the only one in this paper. The object of this research is the texts of the Statutes (of 1529, 1566 and 1588) as such. Therefore, the first chapter of the paper is devoted to the very notion of the “Statute” in legal context of XVI century Lithuanian state, trying to understand, what exactly meant this document for the then Lithuanian civic society. The second and third chapters are related to some historic background of adoption of these documents, trying to explain their very nature and influence of the last Statute of 1588 on the Union of Lublin, i.e. the Union of Lithuanian state with Polish Crown. The last chapter is devoted to idea of parliamentarism in the text of the last (the third) version of the Lithuanian Statute (1588), trying to identify its five features as follows: a) exceptional role of the Sejm (parliament) in country’s legal and political system; b) the Sejm as representation of the then civic nation; c) reguliar elections; d) imperative mandate and e) traditional parliamentarian functions: legislation and taxation. The paper ends with some conclusions, saying that i) the Lithuanian Statutes and especially its last version of 1588 have been adopted as a result of the idea of rule of law, so popular among Lithuanian nobility during Renaissance epoch; ii) rather strong concept of parliamentarism have been found in the text of the 1588 Statute, including remuneration of MPs, representation and traditional legislative competence of the parliament.